Phenomenology‐Based Ethnography for Management Studies and Organizational Analysis - vom Lehn, Dirk (British journal of management, 2019)
This paper introduces phenomenology‐based ethnography as a novel ethnographic approach for research in management studies and organizational analysis and describes three methods that have been developed from this approach: life‐world analytical ethnography, focused ethnography and go‐along ethnography. Phenomenology‐based ethnography has emerged from developments in sociology that draw on ‘social phenomenology’ developed by Alfred Schütz. These developments involve the use of phenomenology‐based ethnographic methods that shift the focus of research onto participants’ subjective experiences of the field further than has been required by other ethnographic approaches. This paper uses a set of dimensions that allow a comparison of these phenomenology‐based methods’ aims, techniques of data collection and analysis, and required effort. These three methods are then compared with current ethnographic methods used in organizational research and management studies. The paper concludes with a discussion that explores and addresses the critique of how phenomenology‐based ethnography conceives the relationship between the researcher and the research subject.